Alzheimer neuropathology without frontotemporal lobar degeneration hallmarks (TAR DNA‐binding protein 43 inclusions) in missense progranulin mutation Cys139Arg. (15th February 2017) - Redaelli, Veronica; Rossi, Giacomina; Maderna, Emanuela; Kovacs, Gabor G.; Piccoli, Elena; Caroppo, Paola; Cacciatore, Francesca; Spinello, Sonia; Grisoli, Marina; Sozzi, Giuliano; Salmaggi, Andrea; Tagliavini, Fabrizio; et al.
Abstract: Null mutations in progranulin gene ( GRN ) reduce the progranulin production resulting in haploinsufficiency and are tightly associated with tau‐negative frontotemporal lobar degeneration with TAR DNA‐binding protein 43‐positive inclusions (FTLD‐TDP). Missense mutations of GRN were also identified, but their effects are not completely clear, in particular unanswered is the question of what neuropathology they elicit, also considering that their occurrence has been reported in patients with typical clinical features of Alzheimer disease. They describe two fraternal twins carrying the missense GRN Cys139Arg mutation affected by late‐onset dementia and we report the neuropathological study of one of them. Both patients were examined by neuroimaging, neuropsychological assessment and genetic analysis of GRN and other genes associated with dementia. The brain of one was obtained at autopsy and examined neuropathologically. One sister presented clinical and MRI features leading to the diagnosis of Alzheimer disease. The other underwent autopsy and the brain showed neuropathological hallmarks of Alzheimer disease with abundant Aβ‐amyloid deposition and Braak stage V of neurofibrillary pathology, in the absence of the hallmark lesions of FTLD‐TDP. Their findings may contribute to better clarify the role of progranulin in neurodegenerative diseases indicating that some GRN mutations, in particular missense ones, may act as strong risk factor for Alzheimer disease rather than induce FTLD‐TDP.